2020
DOI: 10.28982/josam.813042
|View full text |Cite
|
Sign up to set email alerts
|

Complications increase in which type of duodenal diverticulum? A retrospective cohort study

Abstract: Committee with the decision numbered 2013-KAEK-64. All procedures in this study involving human participants were performed in accordance with the 1964 Helsinki Declaration and its later amendments. Etik Kurul Onayı: Bu çalışma Sağlık Bakanlığı İstanbul Medeniyet Üniversitesi Göztepe Eğitim ve Araştırma Hastanesi Klinik Araştırmalar Etik Kurulu tarafından 11.03.2020 tarihinde 2013-KAEK-64 sayılı kararla onaylanmıştır. İnsan katılımcıların katıldığı çalışmalardaki tüm prosedürler, 1964 Helsinki Deklarasyonu ve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The recurrence rate of choledocholithiasis in elderly patients (>65 years) may be as high as 30% [10] . The specific mechanism is not clear, but Akaydin et al [11] suggested that secondary risk factors such as common bile duct dilation and especially PAD, which cause retrograde infection in the papilla, increase the risk of CBDS; this risk is higher in the papillae located within the diverticula. PAD is rare in patients under 40 years of age, and its incidence increases with age.…”
Section: Discussionmentioning
confidence: 99%
“…The recurrence rate of choledocholithiasis in elderly patients (>65 years) may be as high as 30% [10] . The specific mechanism is not clear, but Akaydin et al [11] suggested that secondary risk factors such as common bile duct dilation and especially PAD, which cause retrograde infection in the papilla, increase the risk of CBDS; this risk is higher in the papillae located within the diverticula. PAD is rare in patients under 40 years of age, and its incidence increases with age.…”
Section: Discussionmentioning
confidence: 99%